THE SEVEN CASES UNSTRUCTURED TRIANGULATION TECHNIQUE FOR RADIATIVE HEAT TRANSFER APPROXIMATION IN AN ETHYLENE FURNACE CRACKER - Zuraida , Abal Abas; Zaheera , Zainal Abidin; Abdul Samad , Shibghatullah; Ahmad Fadzli Nizam, Abdul Rahman; Hidayah, Rahmalan; Nur Farraliza, Mansor (2017)
Radiative heat distribution inside an ethylene cracker furnace is often modelled using the finite volume and finite element methods. In both cases, meshes in the form of rectangles and triangles are needed to serve as the approximating points in the domain. In this paper, a new method called the Seven Cases Unstructured Triangulation Technique (7CUTT) is proposed for meshing the domain inside the cracker furnace, integrated with the deployment of sensors on the wall to obtain the boundary value. 7CUTT is an enhanced version of the Standard Advancing Front Technique (SAFT) which two normal cases in SAFT are extended to the total of seven cases for consideration during the element creation procedure for initial mesh generation. The focus of this method is to construct the initial triangular meshes with the requirement of (1) having the location of sensors deployed along the wall as boundary nodes as well as forming boundary elements, (2) generating nodes at a certain boundary with linearly different lengths of boundary edges as interior gradation controls and (3) constructing the triangular element directly in every iteration without having to re-order the Front or delete the existing elements. There are three contributions from this paper, the first one is the introduction of seven extended cases for consideration for the element creation procedure, the second is the layer concept to generate edges with linearly different lengths and the third is the post-processing mesh procedure to improve the quality of the mesh that is suitable for 7CUTT. The final mesh is obtained once the post-processing procedure of improving the mesh quality is applied to the initial mesh. 7CUTT provides the framework for the heat to be approximated using the discrete ordinate method, which is a variant of the finite volume method. Simulation results produced using FLUENT support the findings for effectively approximating the flue gas temperature distribution, the circumferential radiative heat flux incident at the reactor coils as well as the circumferential reactor coil temperature in the furnace at the end of the study.